MICROBIAL SCENERY OF SOYBEAN RHIZOSPHERE UNDER DIFFERENT INOCULANTS INTRODUCTION - Н. І. Адамчук-Чала; Л. В. Титова; Г. О. Іутинська (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
Aim. Investigation of space-functional structure of soybean rhizosphere microbiocenosis under introduction of nodule and phosphate-mobilizing bacteria in the inoculate composition with using of structural analysis of scenery panoramic biofilms. Methods. the new method for investigation of bacteria communities morphological diversity of the not destroy soybean-legume systems was employed. This method is based on using of polymer overgrowth blade with next scan and transmission electron microscope analysis. Results. Structure analysis of microbe scenery panoramic biofilm in sparing regime showed that soybean seeds inoculation by monoculture Bradyrhizobium japonicum UCМ В-6018 or both with Bacillus megaterium UCM В-5724 promoted increasing of rhizospheric bacteria quantity on the square of view and their morphometric parameters. Conclusions. Inoculation of soybean seeds promoted increasing of quantities and morphological characteristics of bacteria populations in the soybean rhizosphere. The greatest effect was obtained in the variant with binary inoculation.